Evaluasi Implementasi Rantai Dingin pada Penyimpanan Vaksin di Puskesmas Kabupaten Murung Raya - Eko Yatminto (Parapemikir : Jurnal Ilmiah Farmasi, 2026)
Vaccines, as biological products, are highly sensitive to temperature fluctuations and therefore require proper cold chain management. However, storage practices in primary healthcare facilities often do not meet established standards. This study aimed to assess the level of compliance of vaccine storage practices in primary healthcare centers in Murung Raya Regency with prevailing national standards. The study employed a quantitative approach with a descriptive-evaluative design. Five primary healthcare centers were purposively selected in September 2025. Data were collected through direct observation using a structured checklist based on national vaccine management guidelines and were analyzed descriptively by calculating the percentage of compliance for each indicator. The results showed that cold chain infrastructure and temperature monitoring fully met the required standards (100%), including the availability of dedicated vaccine refrigerators, temperature monitoring devices, continuous electricity supply, and temperature records within the recommended range. Stock rotation practices based on VVM, FIFO, and FEFO principles were also optimally implemented (100%). However, compliance with the physical arrangement of vaccines inside the refrigerator was low (20%), particularly regarding spacing between packages and the placement of heat- and freeze-sensitive vaccines. These findings indicate a gap between administrative compliance and actual vaccine storage practices in the field. Strengthened technical supervision and periodic evaluation are necessary to ensure optimal vaccine quality and stability.